Upaya Meningkatkan Kreativitas Siswa Melalui Pemanfaatan Barang Bekas sebagai Alternatif Media Alat Ukur - Ulfiani, Hasna; Dwi Saputro, Taufik Widhiyantoro (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2023)
This study aims to increase student creativity through the use of used-goods or plastics as an alternative medium for measuring instruments. The management of used-goods from the environment can be used as a learning medium that can trigger the creativity of students in learning and learning activities. The used items used are paper, cardboard, and single-use food packaging plastic. The study involved class VII C students of Muhammadiyah 2 Mlati Junior High School as the subject of the study determined through purposive random sampling techniques. Data collection techniques use triangulation techniques, namely observation, interviews, and questionnaires/ questionnaires. The data were analyzed quantitative-triangulation with a descriptive approach. The stages of analysis include data collection, data reduction, data presentation, and conclusions. The results showed that there was an increase in the creativity of class VII C students with the number of students in the Excellent category (10%) and the Good category (84%). Thus, the use of used-things is effective as one of the alternative media to increase student creativity